A Critical Analysis of the Transgender Persons (Protection of Rights) Act: Toward Inclusive and Affirmative Legal Reform - Tabassum, Nihal (The Indonesian Institute of Science and Technology Research, 2025)
This article critically examines the Transgender Persons (Protection of Rights) Act, 2018 and its 2022 amendment bill, with a focus on the definitional gaps that hinder its effective implementation. Central to the critique is the Act's failure to provide a clear and inclusive definition of the term